Mitigation of Occult Lung Injury by Pneumonectomy via Minithoracotomy in Mice - Kohno, M.; Watanabe, M.; Izumi, Y.; Tasaka, S.; Kitagawa, Y.; Maruyama, I.; Kobayashi, K. (The Thoracic and Cardiovascular Surgeon, 2012)
Background The systemic and pulmonary inflammatory response associated with pneumonectomy performed via minithoracotomy versus that after open posterolateral thoracotomy is uncertain.Methods Groups consisting of 7 randomly assigned mice underwent a) minithoracotomy (with 5-mm long incisions and sparing of the muscles) alone, b) posterolateral thoracotomy (with 20-mm long incisions) alone, c) pneumonectomy via minithoracotomy, or d) pneumonectomy via posterolateral thoracotomy. The animals' daily food intake, body weight changes and spontaneous activity were monitored for 10 days, and lung water accumulation and vascular hyperpermeability in the remaining right lung were measured at 24 h after surgery. Concentrations of high mobility group box 1 protein (HMGB1), a mediator of inflammation and shock, were measured in the bronchoalveolar lavage fluid.Results Compared with posterolateral thoracotomy, pneumonectomy via minithoracotomy was associated with significantly less weight loss (p < 0.05), despite a similar daily food intake among the groups. Spontaneous activity after pneumonectomy via minithoracotomy returned earlier than after posterolateral thoracotomy. Pulmonary vascular hyperpermeability and water retention in the residual lung were significantly less prominent after pneumonectomy performed via minithoracotomy than after pneumonectomy via posterolateral thoracotomy (both comparisons p < 0.05). HMGB1 concentrations in the bronchoalveolar lavage fluid collected from the residual lung were significantly lower (p < 0.05) after minithoracotomy than after posterolateral thoracotomy.Conclusions Based on postoperative weight loss, spontaneous activity, and the degree of pulmonary capillary injury in the residual lung, pneumonectomy via minithoracotomy was less invasive than posterolateral thoracotomy. The lower increase in HMGB1 associated with minithoracotomy might result in lower pulmonary vascular hyperpermeability and reflect less surgical invasiveness.
Keywords: lung cancer treatment (surgery, medical); minimally invasive surgery (includes port access minithoracotomy); inflammation systemic (incl. cells, mediators); surgery/incisions; thoracoscopy/VATS